A centenary of Robert T. Leiper's lasting legacy on schistosomiasis and a COUNTDOWN on control of neglected tropical diseases. Issue 12 (1st July 2016) - STOTHARD, J. RUSSELL; KABATEREINE, NARCIS B.; ARCHER, JOHN; AL-SHEHRI, HAJRI; TCHUEM-TCHUENTÉ, LOUIS ALBERT; GYAPONG, MARGARET; BUSTINDUY, AMAYA L.
SUMMARY: Part of Robert T. Leiper's (1881–1969) lasting legacy in medical helminthology is grounded on his pioneering work on schistosomiasis (Bilharzia). Having undertaken many expeditions to the tropics, his fascination with parasite life cycles typically allowed him to devise simple preventive measures that curtailed transmission. Building on his formative work with others in Africa and Asia, and again in Egypt in 1915, he elucidated the life cycles of African schistosomes. His mandate, then commissioned by the British War Office, was to prevent and break transmission of this disease in British troops. This he did by raising standing orders based on simple water hygiene measures. Whilst feasible in military camp settings, today their routine implementation is sadly out of reach for millions of Africans living in poverty. Whilst we celebrate the centenary of Leiper's research we draw attention to some of his lesser known colleagues, then focus on schistosomiasis in Uganda discussing why expanded access to treatment with praziquantel is needed now. Looking to WHO 2020 targets for neglected tropical diseases, we introduce COUNTD OWN, an implementation research consortium funded by DFID, UK, which fosters the scale-up of interventions and confirm the current relevance of Leiper's original research.